The Development of Creative Tourism in Kampung Jamu, Banjarbaru City, and Sharia-Based Branding Strategies - MR, Galuh N. Kartika; Erziaty, Rozzana; Hulaify, Akhmad (Mimbar Agama Budaya, 2024)
This research aimed to explore the potential and design development strategies for creative tourism in Kampung Jamu, Banjarbaru, focusing on Sharia-based branding. Using a qualitative case study method, the respondents consisted of 27 jamu entrepreneurs, 2 consumers, and the local RT head, selected through saturation and incidental sampling techniques. Data were collected through interviews and FGDs, and analysed using SWOT. The findings revealed that Kampung Jamu Loktabat had great potential to develop due to its strong reputation, expertise in traditional jamu production, and community support. However, challenges such as regulatory changes, modern competition, and technological advancements needed to be addressed. Opportunities for collaboration, social media promotion, product diversification, and workforce training could help Kampung Jamu maintain its competitiveness and grow as a Sharia-based jamu tourism destination